ANALISIS SWOT PELAKSANAAN PARIWISATA HALAL OLEH DINAS PARIWISATA PROVINSI RIAU - Nelson, Vivi Sepnia; ", Adianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Halal tourism is an additional service provided to meet the experiences, needs and desires of tourists, especially tourists who are Muslim. Halal tourism has a concept of Muslim Friendly. The purpose of this study was to determine and analyze the implementation of halal tourism by the Riau Tourism Office and how to formulate a strategy for halal tourism. This research uses descriptive qualitative research methods. The collection of necessary data, both primary and secondary data, is collected through interviews, observation and documentation and then analyzed so that conclusions can be drawn from existing research problems. Based on the results of the SWOT analysis, the recommended strategy is Agresive Strategy where this situation is very profitable, because the strengths that are owned can be utilized for the opportunities that exist. The results of this study indicate that the implementation of halal tourism through the Riau Tourism Office has not been running optimally and in a deep strategy implementing halal tourism by intensifying publications, increasing supervision, and increasing culinary tourism branches. Keywords: Halal tourism, Strategy, SWOTÂ Â